Integrating Mobile Assisted Language Learning (MALL) in English Courses for Vocational Students at Politeknik Negeri Bengkalis: Insights into Benefits and Barriers - DESI WAHANA (Universitas Maritim Raja Ali Haji (UMRAH), 2025)
This study explores vocational students’ perceptions of Mobile Assisted Language Learning (MALL) in English courses using a mixed-methods design, with data collected from questionnaires completed by 48 students and semi-structured interviews with 12 students and 3 lecturers. The quantitative results indicated favorable attitudes toward the use of mobile technologies, with perceived usefulness achieving the highest mean score (M = 4.21, SD = 0.54), as 85% of respondents agreed that MALL made English lessons more practical and relevant to professional contexts. Motivation was also positively rated (M = 4.05, SD = 0.61), with 78% acknowledging that mobile applications increased their engagement and interest, while learning outcomes (M = 4.08, SD = 0.59) were seen as beneficial in enhancing vocabulary, pronunciation, and communication skills. Accessibility received moderately favorable ratings (M = 3.92, SD = 0.73), reflecting both the advantage of flexible learning and challenges related to unstable internet connections and limited device storage. Qualitative findings reinforced these insights, revealing five central themes: increased engagement and learner autonomy fostered by interactive features, development of communication skills through authentic workplace-like practices, technological limitations such as connectivity issues and unequal device access, differences in digital literacy that highlighted the need for training, and the importance of institutional and pedagogical support to ensure sustainability. Overall, the study concludes that MALL is perceived as an effective and relevant approach to English learning in vocational contexts, as it promotes autonomy, motivation, and skill development. However, for MALL to be fully effective, it is essential to address technological barriers, strengthen students’ digital competence, and provide continuous institutional and pedagogical support to integrate it as an essential component of vocational English education.